Absorbable antibacterial oral repair membrane material as well as preparation method and application thereof

By combining polyester copolymer, polylysine and minerals and using electrospinning technology to prepare oral restoration membrane materials, the problems of uneven material performance and poor antibacterial effects in the prior art have been solved, and the biosafety, antibacterial properties and mechanical properties of the membrane materials have been improved.

CN119792632APending Publication Date: 2025-04-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311297784.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing oral restorative membrane materials have shortcomings in promoting bone repair and antibacteriality, and it is difficult to prepare membrane materials with uniform thickness and uniform fiber structure, which affects its mechanical properties and application effects.

Method used

The combination of polyester copolymer, polylysine and minerals (such as hydroxyapatite, β-calcium phosphate) is used to prepare a film material composed of micro-nano-grade fibers through electrospinning technology to ensure the uniformity of the fiber structure and the uniformity of the film thickness.

Benefits of technology

It has achieved the improvement of the biosafety and antibacterial properties of membrane materials, and at the same time it has improved its mechanical properties and repair effects in degradation and application, and has high mechanical strength and application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119792632A_ABST
    Figure CN119792632A_ABST
Patent Text Reader

Abstract

The invention relates to the field of repair materials, and discloses an absorbable antibacterial oral repair membrane material as well as a preparation method and application thereof. The membrane material contains a polyester copolymer, polylysine and mineral substances, wherein the polyester copolymer contains a polyethylene glycol chain segment and a degradable polyester chain segment; the membrane material is composed of micro-nano fibers, the average diameter of the fibers is 100 nm to 10 [mu] m, and the pore range of the membrane is 100 nm to 50 [mu] m; the thickness of the membrane material is 100-900 [mu] m, and the uniformity is + / -30 [mu] m. The membrane material has the effects of promoting bone repair and resisting bacteria, and more importantly, the membrane material disclosed by the invention is good in membrane forming property, very uniform in thickness, more uniform in fiber structure in the membrane and free from a phase separation phenomenon, so that the degradation property and the mechanical property of the membrane material tend to be consistent in the degradation and application processes; meanwhile, the film has certain mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of repair materials, and in particular to an absorbable antibacterial oral repair membrane material and a preparation method and application thereof. Background Art

[0002] Oral repair membranes are widely used in the regeneration and repair of alveolar bone defects. Currently, oral repair membranes mainly use collagen materials, but collagen is generally considered to only play an isolating role and has no function of promoting bone regeneration and repair. At the same time, there are a large number of bacteria in the oral cavity, which can easily lead to wound infection and hinder the regeneration and repair of alveolar bone. Therefore, it is of great significance to develop oral repair membranes that promote bone repair and have antibacterial effects.

[0003] Patent CN 113797395 A discloses a composite material of nano-hydroxyapatite / block copolymer and a preparation method thereof. The composite material comprises nano-hydroxyapatite and polyester block copolymer, and the block copolymer comprises a PLA PEG PLA block copolymer composed of polyethylene glycol segments and polylactide segments. The block copolymer (number average molecular weight 4000-12000) and polyethylene glycol molecular weight (number average molecular weight 1000-3500) used in the composite material are relatively low, and the obtained composite material is amorphous, i.e., cannot form a film, which is limited in application.

[0004] The document "Facile Stem Cell Delivery to Bone Grafts Enabled by SmartShapeRecovery and Stiffening of Degradable Synthetic Periosteal Membranes" mentions that a PLGA-PEG-PLGA block copolymer composed of polyethylene glycol segments and polylactide-glycolide can be combined with hydroxyapatite to prepare a spinning membrane with a micro-nano fiber structure. However, after further research, the inventors of the present invention found that the spinning uniformity obtained by this material is poor, and particles are prone to appear during spinning, phase separation occurs, and the performance of the membrane is uneven. Moreover, the spinning membrane obtained by the method in this document is thick in the middle and thin around, and the uniformity of the membrane thickness and the effective use area are low, which affects the overall mechanical properties of the membrane.

[0005] In addition, as mentioned above, there are a large number of bacteria in the oral cavity, which can easily lead to wound infection and hinder the regeneration and repair of alveolar bone. The addition of conventional antibacterial agents often introduces uncertain factors to the performance of the repair film, such as making film formation more difficult and reducing the mechanical strength of the film.

[0006] Therefore, how to prepare a film that has excellent biosafety and antibacterial properties, and can combine minerals that promote bone repair with degradable polymers to form a film with uniform fiber structure, no phase separation, good film-forming properties, and a certain mechanical strength, is a difficult problem that needs to be overcome in this field. Summary of the invention

[0007] In view of the above technical problems, the purpose of the present invention is to provide an absorbable antibacterial oral repair membrane material and a preparation method and application thereof. The membrane material contains a degradable polymer, minerals that promote bone repair and polylysine as an antibacterial agent. It not only has the effects of promoting bone repair and antibacterial, but more importantly, the membrane material of the present invention has good film-forming properties, very uniform thickness, a more uniform fiber structure in the membrane, and no phase separation phenomenon, so that the degradation performance and mechanical properties of the membrane material tend to be consistent during the degradation and application process, and the membrane also has a certain mechanical strength.

[0008] The inventors of the present invention have found through research that if a degradable polymer such as polylactic acid (such as PLLA) is combined with minerals that promote bone repair, such as hydroxyapatite and β-calcium phosphate, it is expected to prepare a composite functional membrane with better biosafety. However, polylactic acid has a hydrophobic nature, and the membrane performance obtained by combining it with hydroxyapatite and β-calcium phosphate micro-nano particles is not ideal. The above-mentioned membrane performance is not ideal. On the one hand, it is reflected in the poor uniformity of the thickness of the obtained membrane, resulting in poor overall mechanical properties of the material. On the other hand, the minerals that promote bone repair are unevenly dispersed in the membrane, and a granular structure appears, so that its repair effect in application needs to be improved.

[0009] The first aspect of the present invention is to provide a membrane material, comprising a polyester copolymer, polylysine and minerals, wherein the polyester copolymer comprises a polyethylene glycol segment and a degradable polyester segment; the degradable polyester segment is derived from one of the following cyclic ester monomers: lactide, caprolactone, valerolactone, butyrolactone;

[0010] The membrane material is composed of micro-nano-scale fibers, the average diameter of the fibers is 100nm-10μm, and the membrane pore range is 100nm-50μm; the thickness of the membrane material is 100-900μm, and the uniformity is ±30μm.

[0011] In a preferred embodiment of the present invention, the thickness of the membrane material is 100-200 μm.

[0012] In a preferred embodiment of the present invention, a film material with a size of 5mm*60mm and a thickness of 170μm±30μm is used as a test sample. The tensile breaking force of the test sample is tested under the conditions of an initial length of 30mm and a tensile rate of 100mm / min. The tensile breaking force of the film material is not less than 1N.

[0013] In a preferred embodiment of the present invention, the content of polylysine in the membrane material is 0.00001-0.0005 parts, and the content of the mineral is 0.09-0.55 parts, relative to 1 part of the polyester copolymer, by mass. More preferably,

[0014] In parts by mass, relative to 1 part of the polyester copolymer, the content of polylysine in the membrane material is 0.00005-0.0001 part, and the content of the mineral is 0.1-0.5 part.

[0015] In a preferred embodiment of the present invention, the number average molecular weight of the polyethylene glycol segment in the polyester copolymer is 5,000-50,000, preferably 10,000-20,000.

[0016] In a preferred embodiment of the present invention, the molar ratio of the structural units in the polyethylene glycol segment to the structural units in the degradable polyester segment is (1:250)-(1:7000), preferably (1:700)-(1:4000).

[0017] In a preferred embodiment of the present invention, the number average molecular weight of the polyester copolymer is 20,000-500,000. Preferably, the polyester copolymer is obtained by polymerizing polyethylene glycol and a cyclic ester monomer in the presence of a catalyst in a protective atmosphere.

[0018] In a preferred embodiment of the present invention, the mineral is selected from at least one of hydroxyapatite, calcium phosphate, calcium carbonate, strontium and magnesium; and / or the particle size range of the mineral is <500 nm.

[0019] In a preferred embodiment of the present invention, the polylysine is ε-polylysine, and preferably, the number average molecular weight of the ε-polylysine is 3000-50000, preferably 3000-10000.

[0020] In a preferred embodiment of the present invention, the membrane material is prepared by electrospinning a mixed solution comprising the polyester copolymer, polylysine, minerals and a solvent; the electrospinning conditions include:

[0021] The electrospinning mixed solution is sprayed onto the rotating drum by using a nozzle, and the nozzle reciprocates along the axial direction of the drum;

[0022] The movement speed of the nozzle is 0.8-100mm / s, the rotation speed of the drum is 100-1000rpm; the ratio of the flow rate of the mixed liquid to the nozzle diameter is 2-244mL / h / mm;

[0023] The mass dosage ratio of the polyester copolymer to the volume dosage of the solvent is 0.15-0.18 g / ml.

[0024] As mentioned above, the hydrophilic and hydrophobic properties of degradable polymers and minerals such as hydroxyapatite and β-calcium phosphate are different. It is difficult to disperse the two evenly to prepare a uniform product, and it is even more difficult to prepare a uniform membrane material. Even if the problem of uneven mixing of degradable polymers and minerals is overcome by modification, and membrane materials can be prepared, it is still difficult to obtain uniform thickness and micro-nano fiber membranes, because film formation is often affected by many factors. Taking electrospinning membrane as an example, membrane preparation is restricted by many conditions such as component raw materials, component ratios, electrospinning liquid ratios, electrospinning methods (such as how the nozzle extrudes and the extrusion flow rate), and solvent types. It is difficult to obtain a membrane material composed of micro-nano fibers, let alone a membrane material with uniform thickness. In addition, the solution containing degradable polymers, minerals and polylysine is not a uniform solution, which further increases the difficulty of preparing the above membrane materials.

[0025] The inventor of the present invention has found through research that the introduction of polar polyethylene glycol segments into degradable polymers such as poly-L-lactic acid can enhance the interaction between polymers and inorganic substances and improve the compatibility of polymers and minerals by forming hydrogen bonds between oxygen in polyethylene glycol and hydroxyl groups on the surface of minerals such as hydroxyapatite and β-calcium phosphate particles. Using the specific raw materials of the present invention, polyester copolymer, polylysine, minerals and solvents (preferably the solvent is selected from at least one of chloroform, N, N-dimethylformamide, dichloromethane, tetrahydrofuran, acetonitrile, preferably chloroform and N, N-dimethylformamide), under the condition that the specific nozzle and receiver of the present invention are uniformly moving, using a specific extrusion flow rate and a specific ratio of the electrospinning solution, a membrane material composed of micro-nanoscale fibers with uniform thickness can be obtained, and the fiber structure has no phase separation phenomenon. It also means that the repair performance and uniformity of mechanical properties of the membrane material of the present invention have been significantly improved, and it has extremely high value in application.

[0026] The second aspect of the present invention is to provide a method for preparing the membrane material described in the first aspect, comprising electrospinning a mixed solution comprising the polyester copolymer, polylysine, minerals and a solvent to obtain the membrane material; the electrospinning conditions include:

[0027] The electrospinning mixed solution is sprayed onto the rotating drum by using a nozzle, and the nozzle reciprocates along the axial direction of the drum;

[0028] The movement speed of the nozzle is 0.8-100 mm / s, the rotation speed of the drum is 100-1000 rpm; the ratio of the flow rate of the mixed liquid to the nozzle diameter is 2-244 mL / h / mm.

[0029] The mass dosage ratio of the polyester copolymer to the volume dosage of the solvent is 0.15-0.18 g / ml.

[0030] In a preferred embodiment of the present invention, the amount of polylysine is 0.00001-0.0005 parts, and the amount of the mineral is 0.09-0.55 parts, relative to 1 part of the polyester copolymer, by weight. More preferably,

[0031] In parts by mass, relative to 1 part of the polyester copolymer, the amount of polylysine in the membrane material is 0.00005-0.0001 parts, and the amount of the mineral is 0.1-0.5 parts.

[0032] Polyester copolymers are easily dissolved in weak polar solvents such as chloroform, but weak polar solvents have poor affinity with polylysine and hydroxyapatite, and have low dielectric constants, which are not conducive to the formation of electrospun fibers. Polar solvents such as N,N-dimethylformamide have high dielectric constants, which help to form electrospun fiber films, and can also improve affinity with polylysine and hydroxyapatite, but such solvents have poor solubility in polymers, so selecting a suitable solvent and the ratio of solvents is a key point and difficulty of the present invention. In a preferred embodiment of the present invention, the solvent is selected from at least one of chloroform, N,N-dimethylformamide, dichloromethane, tetrahydrofuran, and acetonitrile, preferably chloroform and N,N-dimethylformamide, and more preferably the volume ratio of chloroform to N,N-dimethylformamide is (4-10):1.

[0033] In a preferred embodiment of the present invention, the electrospinning conditions include:

[0034] The voltage used for electrospinning is 10-30 kV, preferably 15-25 kV; and / or, the extrusion flow rate of the mixed solution is 0.5-50 mL / h; and / or,

[0035] The rotation speed of the drum is 300-800 rpm; and / or,

[0036] The movement speed of the nozzle is 1-100 mm / s; and / or,

[0037] The total time used for electrospinning is 30 min-12 h, preferably 30 min-8 h.

[0038] The extrusion flow rate of the mixed liquid in the present invention is 0.5-50mL / h. As mentioned above, a low value of 0.5mL / min or a high value of 50mL / h can be used. 0.5, 1, 5, 10, 20, 30, 40, 50mL / h, and any two values ​​or any interval between any two values ​​can also be used as the flow rate, which shows that the preparation method of the present invention is easier to control.

[0039] As an example, the process route of the present invention can be as follows:

[0040]

[0041] The preparation method comprises:

[0042] Step 1, adding the polyethylene glycol into a reaction bottle, heating to 100° C. under vacuum conditions, stirring for 2 hours, and then cooling to room temperature.

[0043] Step 2, adding a catalyst into a reaction bottle under the protection of an inert gas and / or nitrogen, heating to 100° C. under vacuum conditions, stirring for 15 minutes, and then cooling to room temperature.

[0044] Step 3, add cyclic ester monomer to the reaction bottle under the protection of inert gas and / or nitrogen, evacuate and fill with inert gas three times, heat to 100-200° C. under the protection of inert gas and / or nitrogen, react for 4 hours, and then cool to room temperature.

[0045] Step 4, adding a solvent into the reaction bottle, precipitating the polymer solution in ether, filtering and drying to obtain a polyester copolymer.

[0046] Step 5: The synthesized polyester copolymer, ε-polylysine and mineral micro-nano particles are mixed and electrospun into a porous film using a specific method of the present invention.

[0047] Based on the above scheme, the number average molecular weight of the polyethylene glycol in step 1 is 5000-50000, preferably 10000-20000. One or both ends of the polyethylene glycol contain hydroxyl groups.

[0048] Based on the above scheme, the catalyst in step 2 is at least one of stannous isooctanoate, stannous octoate, bis(N,N-bis(trimethylsilyl)amino)zinc, diethylzinc, and tributylaluminum; and / or the mass ratio of the catalyst to the cyclic ester monomer is 1:(2000-4000).

[0049] Based on the above scheme, the cyclic ester monomer in step 3 is a cyclic ester monomer such as lactide, caprolactone, valerolactone, butyrolactone, etc.

[0050] On the basis of the above scheme, the molar ratio of the structural unit in ethylene glycol to the cyclic ester monomer in step 3 is 1:125-1:3500, preferably 1:350-1:2000; the reaction temperature of the ring-opening polymerization is 100-200°C, preferably 100-160°C.

[0051] The third aspect of the present invention is to provide a membrane material according to the first aspect, or a membrane material prepared by the preparation method according to the second aspect, for use as a medical repair material;

[0052] Preferably, the membrane material is used as an oral restoration membrane material.

[0053] The present invention adopts electrospinning to prepare a composite fiber membrane with a micro-nano structure, and simultaneously adds polylysine to increase the antiseptic and antibacterial properties of the composite material. Combining polylysine with an absorbable oral repair membrane based on a synthetic degradable polymer can increase the shelf life of the repair membrane and improve the regeneration and repair of the alveolar bone.

[0054] The membrane material of the present invention can be used as a type of absorbable antibacterial oral repair membrane: the repair membrane contains a copolymer of degradable polyester and polyethylene glycol, polylysine, and minerals such as hydroxyapatite and beta-calcium phosphate, etc. The repair membrane has a micro-nano fiber structure.

[0055] The product of the present invention has a white or light yellow film appearance.

[0056] It can be seen from the above-mentioned content of the invention that the membrane material of the present invention contains polyester copolymer, polylysine and minerals, wherein the polyester copolymer contains polyethylene glycol segments and degradable polyester segments; the membrane material is composed of micro-nano-scale fibers, the fiber diameter is 100nm-10μm, and the membrane pore range is 100nm-50μm; the uniformity of the thickness of the membrane material is ±30μm. The membrane material contains degradable polymers, minerals that promote bone repair, and polylysine as an antibacterial agent, which not only has the effect of promoting bone repair and antibacterial, but also has good film-forming properties, very uniform thickness, and more uniform fiber structure in the membrane, so that the degradation performance and mechanical properties of the membrane material tend to be consistent during degradation and application, and the membrane has a certain mechanical strength.

[0057] In summary, the present invention introduces hydrophilic polyethylene glycol segments into the degradable polyester and introduces ε-polylysine into the film-making raw materials, thereby improving the compatibility of the degradable polyester with inorganic minerals and improving the properties of the material to form fibers and films, thereby improving the bone repair and antibacterial properties of the oral repair membrane. Description of the drawings:

[0058] Figure 1 The electrospun membrane and its microstructure obtained in Example 1 are shown in FIG. Figure 1 It can be seen that the spun membrane is uniform, flat and defect-free, with the thickness of the middle and edge being 170μm and 150μm respectively, the fiber structure being uniform without phase separation, the diameter being approximately 100nm-4μm, and the gap being approximately 800nm-9μm.

[0059] This indicates that under this condition, micro-nano fiber films with uniform thickness and good fiber formability can be successfully prepared. DETAILED DESCRIPTION

[0060] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0061] In the following embodiments:

[0062] Method for detecting the number average molecular weight: 1 mg of the polymer was dissolved in 1 mL of tetrahydrofuran, stirred for 12 h to fully dissolve, and then the molecular weight of the polymer in the solution was tested by gel permeation chromatography (GPC).

[0063] The method for detecting the thickness of the film is: using a vernier caliper to test the thickness of different parts of the film.

[0064] The average fiber diameter of the film is measured by cutting the film into small pieces, coating the surface with 8nm thick gold, and observing it under a scanning electron microscope (SEM) with an accelerating voltage of 15KV. Take 50 fibers from the SEM image to test their diameters and calculate their average value.

[0065] The average pore size of the film is tested by cutting the film into small pieces, coating the surface with 8nm thick gold, and observing it under a scanning electron microscope (SEM) with an accelerating voltage of 15KV. Take 50 fiber network pores in the SEM image to test their size and calculate their average value.

[0066] The testing method of the mechanical strength of the film is as follows: the film is cut into rectangles with a width of 5 mm and a length of 60 mm, and its tensile breaking strength is tested by stretching, the stretching rate is 100 mm / min, and the test starting length is 30 mm.

[0067] The method for testing the uniformity of the thickness of the film material is: using a vernier caliper to test the thickness of the center and edge of the film.

[0068] The electrospinning device used in the following examples and comparative examples is Lepton Nano E02-001, and the electrospinning device comprises: a pump and a needle for spraying the spinning solution;

[0069] A drum receiver is used to receive the spinning solution ejected from the needle;

[0070] The length direction of the needle is perpendicular to the axial direction of the roller, and the needle can reciprocate at a uniform speed along the axial direction of the roller, and the roller can rotate at a uniform speed around the axis of the roller.

[0071] In the following examples, the number average molecular weight of ε-polylysine is 3800-4200;

[0072] The particle size range of hydroxyapatite is <100 nm.

[0073] Example 1

[0074] Steps:

[0075] Step 1, add 2 g of polyethylene glycol with a number average molecular weight of 20,000 and hydroxyl groups at both ends into a dry reaction bottle, heat to 100° C. under vacuum conditions, stir for 2 hours, and then cool to room temperature.

[0076] Step 2, add 3 mg of stannous isooctanoate into the reaction bottle under nitrogen protection, evacuate and heat to 100° C., stir for 15 minutes, and then cool to room temperature.

[0077] Step 3, add 8 g of dry L-lactide into the reaction bottle under nitrogen protection, evacuate and fill with nitrogen three times, heat to 140° C. under nitrogen protection, stir and react for 4 hours, and then cool to room temperature.

[0078] Step 4, add 60 mL of chloroform to the reaction bottle, precipitate the polymer solution in 500 mL of 0° C. ether, filter and dry in a vacuum oven for 72 hours to obtain a polymerization product, and the number average molecular weight of the polymer is measured to be 49905.

[0079] Step 5, 1 g of the synthesized polymer, 100 μg of ε-polylysine and 0.43 g of hydroxyapatite were dissolved in 5 mL of chloroform / 1 mL of N,N-dimethylformamide, stirred overnight and fully mixed, and then loaded into a 5 mL syringe. The syringe was connected to the needle and placed about 15 cm from the roller receiver.

[0080] A high voltage power supply was used to apply 17 kV voltage to the needle (needle diameter was 0.41 mm), and the needle moved back and forth along the axis of the drum at a rate of 1 mm / s. The receiving drum rotated at 300 rpm, and the mixed solution was extruded and spun at a rate of 2 mL / h by a pump. After spinning for 2.5 hours, the obtained porous spun film was placed in a vacuum oven for 72 hours to dry to obtain a spun film.

[0081] The obtained spinning film has a center thickness of 170 μm, an edge thickness of 150 μm, an average fiber diameter of 0.75 μm, an average pore size of 3.8 μm, and a maximum tensile breaking force of 1.13N.

[0082] Example 2

[0083] The spinning film was prepared according to the method of Example 1, except that 1 g of the polymer synthesized in step 4 of Example 1, 100 μg of ε-polylysine and 0.25 g of hydroxyapatite were dissolved in 5 mL of chloroform / 1 mL of N,N-dimethylformamide, stirred overnight to mix thoroughly, and then loaded into a 5 mL syringe. The syringe was connected to the needle and placed about 15 cm from the roller receiver.

[0084] A high voltage power supply was used to apply 17 kV voltage to the needle (needle diameter was 0.41 mm), and the needle moved back and forth along the axis of the drum at a rate of 1 mm / s. The receiving drum rotated at 300 rpm, and the mixed solution was extruded and spun at a rate of 10 mL / h by a pump. After spinning for 0.5 h, the obtained porous spun film was placed in a vacuum oven for 72 hours to dry to obtain a spun film.

[0085] The obtained spinning film has a center thickness of 180 μm, an edge thickness of 170 μm, an average fiber diameter of 1.2 μm, an average pore size of 6.1 μm, and a maximum tensile breaking force of 1.20N.

[0086] Example 3

[0087] The spinning film was prepared according to the method of the embodiment, except that, in step 1, 1 g of the polymer synthesized in step 4 of embodiment 1, 50 μg of ε-polylysine and 0.11 g of hydroxyapatite were dissolved in 5 mL of chloroform / 1 mL of N,N-dimethylformamide, stirred overnight and fully mixed, and then loaded into a 5 mL syringe. The syringe was connected to the needle and placed about 15 cm from the roller receiver.

[0088] A high voltage power supply was used to apply 17 kV voltage to the needle (needle diameter was 0.41 mm), and the needle moved back and forth along the axis of the drum at a rate of 1 mm / s. The receiving drum rotated at 300 rpm, and the mixed solution was extruded and spun at a rate of 10 mL / h by a pump. After spinning for 0.5 h, the obtained porous spun film was placed in a vacuum oven for 72 hours to dry to obtain a spun film.

[0089] The obtained spinning film has a center thickness of 170 μm, an edge thickness of 160 μm, an average fiber diameter of 1.1 μm, an average pore size of 7.8 μm, and a maximum tensile breaking force of 1.33N.

[0090] Comparative Example 1

[0091] The spun film was prepared according to the method of Example 1, except that the solvent was 6 mL chloroform / 1 mL N,N-dimethylformamide and the electrospinning time was 175 min.

[0092] The obtained spinning film had a center thickness of 180 μm and an edge thickness of 160 μm. The fibers showed phase separation, an average diameter of 0.96 μm, an average pore size of 6.5 μm, and a maximum tensile breaking force of 0.81 N (reduced).

[0093] Comparative Example 2

[0094] The electrospun membrane was prepared according to the method of Example 1, except that the mixed liquid extrusion flow rate was 1 mL / h, the applied voltage was 14 kV, and the electrospinning time was 5 h. The obtained spun membrane had a center thickness of 180 μm and an edge thickness of 150 μm, the fibers showed phase separation, the average diameter was 1.43 μm, the average pore size was 8.93 μm, and the maximum tensile breaking force was 0.75 N.

[0095] Comparative Example 3

[0096] The electrospun membrane was prepared according to the method of Example 1, except that the needle was stationary and the movement rate was 0 mm / s. The obtained spinning film had a center thickness of 300 μm, an edge thickness of 50 μm, an average fiber diameter of 2.71 μm, an average pore size of 2.64 μm, and a maximum tensile breaking force of 0.30 N.

[0097] Comparative Example 4

[0098] An electrospun membrane was prepared according to the method of Example 1, except that the mass of hydroxyapatite was changed to 0.25 g, the needle was stationary, the movement rate was 0 mm / s, and the roller receiving plate was changed to a flat receiving plate. The resulting spun film had a center thickness of 320 μm, an edge thickness of 30 μm, an average fiber diameter of 1.25 μm, an average pore size of 7.59 μm, and a maximum tensile breaking force of 0.37 N.

[0099] Comparative Example 5

[0100] An electrospun membrane was prepared according to the method of Example 1, except that the mass of hydroxyapatite was changed to 0.11 g, the needle was stationary, the movement rate was 0 mm / s, and the roller receiving plate was changed to a flat receiving plate. The resulting spun film had a center thickness of 310 μm and an edge thickness of 30 μm. The average fiber diameter was 2.54 μm, the average pore size was 12.10 μm, and the maximum tensile breaking force was 0.38 N.

[0101] Comparative Example 6

[0102] The electrospun membrane was prepared according to the method of Example 1, except that 0.72 g of glycolide was additionally added in step 3. Other conditions were the same as those of Example 1.

[0103] A granular structure appeared on the electrospun membrane fiber, and the obtained film had a center thickness of 170 μm and an edge thickness of 160 μm. The average fiber diameter was 2.68 μm, the average pore size was 8.47 μm, and the maximum tensile breaking force was 0.78N.

[0104] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

[0105] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0106] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0107] The endpoints and any values ​​of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.

[0108] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

[0109] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.

Claims

1. A membrane material comprising a polyester copolymer, polylysine and minerals, wherein the polyester copolymer comprises a polyethylene glycol segment and a degradable polyester segment; the degradable polyester segment is derived from one of the following cyclic ester monomers: lactide, caprolactone, valerolactone, butyrolactone; The membrane material is composed of micro-nano-scale fibers, the average diameter of the fibers is 100nm-10μm, and the membrane pore range is 100nm-50μm; the thickness of the membrane material is 100-900μm, and the uniformity is ±30μm.

2. The membrane material according to claim 1, characterized in that: The thickness of the membrane material is 100-200 μm; and / or, In parts by mass, relative to 1 part of the polyester copolymer, the content of polylysine in the membrane material is 0.00001-0.0005 parts, and the content of the mineral is 0.09-0.55 parts; preferably, In parts by mass, relative to 1 part of the polyester copolymer, the content of polylysine in the membrane material is 0.00005-0.0001 part, and the content of the mineral is 0.1-0.5 part.

3. The membrane material according to claim 1, characterized in that: The number average molecular weight of the polyethylene glycol segment in the polyester copolymer is 5000-50000, preferably 10000-20000; and / or, The molar ratio of the structural units in the polyethylene glycol segment to the structural units in the degradable polyester segment is (1:250)-(1:7000), preferably (1:700)-(1:4000); and / or, The number average molecular weight of the polyester copolymer is 20,000-500,000. Preferably, the polyester copolymer is obtained by polymerizing polyethylene glycol and cyclic ester monomers in the presence of a catalyst in a protective atmosphere.

4. The membrane material according to claim 1, characterized in that: The mineral is selected from at least one of hydroxyapatite, calcium phosphate, calcium carbonate, strontium and magnesium; and / or, the particle size of the mineral is in the range of <500 nm; and / or, The polylysine is ε-polylysine. Preferably, the number average molecular weight of the ε-polylysine is 3000-50000, preferably 3000-10000.

5. The membrane material according to any one of claims 1 to 4, characterized in that: The membrane material is prepared by electrospinning a mixed solution comprising the polyester copolymer, the polylysine, the mineral and a solvent; the electrospinning conditions include: The mixed liquid is sprayed onto the rotating drum by a spray head, and the spray head reciprocates along the axial direction of the drum; The movement speed of the nozzle is 0.8-100mm / s, the rotation speed of the drum is 100-1000rpm; the ratio of the flow rate of the mixed liquid to the nozzle diameter is 2-244mL / h / mm; The mass dosage ratio of the polyester copolymer to the volume dosage of the solvent is 0.15-0.18 g / ml.

6. A method for preparing a membrane material according to any one of claims 1 to 5, comprising electrospinning a mixed solution comprising the polyester copolymer, polylysine, minerals and a solvent to obtain the membrane material; the electrospinning conditions comprising: The mixed liquid is sprayed onto the rotating drum by a spray head, and the spray head reciprocates along the axial direction of the drum; The movement speed of the nozzle is 0.8-100mm / s, the rotation speed of the drum is 100-1000rpm; the ratio of the flow rate of the mixed liquid to the nozzle diameter is 2-244mL / h / mm; The mass dosage ratio of the polyester copolymer to the volume dosage of the solvent is 0.15-0.18 g / ml.

7. The preparation method according to claim 6, characterized in that: In parts by mass, relative to 1 part of the polyester copolymer, the amount of polylysine is 0.00001-0.0005 parts, and the amount of the mineral is 0.09-0.55 parts; preferably, In parts by mass, relative to 1 part of the polyester copolymer, the amount of polylysine used is 0.00005-0.0001 part, and the amount of the mineral used is 0.1-0.5 part.

8. The preparation method according to claim 6, characterized in that: The solvent is selected from at least one of chloroform, N,N-dimethylformamide, dichloromethane, tetrahydrofuran and acetonitrile, preferably chloroform and N,N-dimethylformamide, more preferably the volume ratio of chloroform to N,N-dimethylformamide is (4-10):

1.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The electrospinning conditions include: The voltage used for electrospinning is 10-30 kV, preferably 15-25 kV; and / or, the extrusion flow rate of the mixed solution is 0.5-50 mL / h; and / or, The rotation speed of the drum is 300-800 rpm; and / or, The movement speed of the nozzle is 1-100 mm / s; and / or, The total time used for electrospinning is 30 min-12 h, preferably 30 min-8 h.

10. Use of the membrane material according to any one of claims 1 to 5, or the membrane material prepared by the preparation method according to any one of claims 6 to 9 as a medical repair material; Preferably, the membrane material is used as an oral restoration membrane material.

Citation Information

Patent Citations

  • Nano-hydroxyapatite / block copolymer composite material and preparation method thereof

    CN113797395A